Religious Changes and Cultural Transformations in the Early Modern Western Sephardic Communities - Kaplan, Yosef (Studies in Jewish History and Culture, 2019)
The Western Sephardic communities came into being as a result of confessional migration. However, in contrast to the other European confessional communities, the Sephardic Jews in Western Europe came to Judaism after a separation of generations from the religion of their ancestors. The contributions in this volume detail those transformations in the Early Modern Western Sephardic communities. Readership: All interested in Early Modern Jewish History and Sephardic Studies, and anyone concerned with the process of confessionalization in Europe during the sixteenth and seventeenth centuries.